DISAIN PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DAN RE-USE AIR DI LINGKUNGAN PERHOTELAN - Setiyono, Setiyono (Center for Environmental Technology, 2009)
Denpasar is one of the number one tourist destination in the world. This city needs a lot of water resources with high quality to meet the needs of the hotel. While the Bali island with a relatively small area can not save the water resources in large numbers, the good management of water resources and efficiency use of water is realy needed. Hotel is one of the largest water users in the city of Denpasar. The water source is from deep ground water and PDAM with the same quality. If someday deficit water and sea water intrusion in Denpasar happened, the hotel will be accused as one major cause of this problem. To overcome these problems, environmentally friendly hotel management will be needed to achieve